“The Lost Princess (putri duyung)” of the Small Islands: Dugongs around Sulawesi in the Anthropocene - Moore, Abigail M.; Ambo-Rappe, Rohani; Ali, Yusuf (Frontiers in Marine Science, 2017)
In the Spermonde as in the other main island groups around Sulawesi, seagrass and coral ecosystems are intimately linked ecologically and overlap extensively on the shallow water shelves surrounding most islands. One keystone species living in these shallow waters is the dugong (Dugong dugon). Officially fully protected under Indonesian Law (PP7/1999), published data on dugongs in the islands around Sulawesi are extremely limited. In this research, we collected, compiled and evaluated data and information (mostly unpublished) on the distribution, exploitation and community perceptions of dugongs around Sulawesi, including the Togean, Banggai, Spermonde, Taka Bone Rate/Selayar and Tanakeke Islands. Opportunities for dugong conservation, and potential benefits for coral reef ecosystems in a small island socio-ecological context, were considered. Once common within living memory, socio-economic data indicate that Sulawesi dugongs are now rare and under severe threat. Many fishing communities consider dugong meat superior to beef, and see it as a welcome change from fish, while certain body parts fetch a high price, as do dugong tears. In the Spermonde Islands, dugongs may already have been extirpated; the most recent reported sighting was in 1993 when the capture of an adult dugong by fishermen of Barranglompo Island resulted in an impromptu festival. All these Sulawesi small islands communities have dugong princess (putri duyung) legends with potential as an entry-point to hearts and minds. Preventing further extirpations and striving to bring back the “lost princess” could be an iconic component of moving towards sustainability in small-island socio-ecological systems.